Tree Diversity of the Tropical Montane Evergreen forest (SHOLA) in the Nilgiri Mountains, Western Ghats, India - Anbarasu, C.; Balasubramanian, P. (Indian Forester, 2015)
Tree diversity in tropical montane evergreen forest (shola) in the Nilgiri mountains, which is a unique ecosystem of the Western Ghats was enumerated. Two one hectare plots were established in the study sites of Longwood (LD) and Eppanadu (ED), in which all trees >20cm girth at breast height (GBH) were noted. Fifty five tree species belonging to 35 families were reported. Site ED harboured 7.3% greater species richness than LD. Species diversity did not vary much between the two sites. 874 individuals of 38 genera and 45 species of trees were encountered in site LD, whereas in ED 1013 individuals belonging to 39 genera and 46 species were recorded. Twenty two endemic tree species were encountered in the study sites. Lauraceae was highly dominant family.